ANALISIS KARAKTERISTIK USAHA DAN DEBITUR UMKM UNTUK MENEKAN RISIKO KREDIT MACET (Studi Kasus pada debitur UMKM Bank Jatim Cabang Blitar) - Vega, Gabriela Lovita De (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to determine the effect of business characteristics and the debtor on the return of credit by the debtor MSMEs. Non performing loans are loans that repayment of loan principal and interest payments have been delayed more than a year since the due date according to the agreed schedule. The approach used in this study is a qualitative case study method. Researcher using purposive sampling method. Peoples who to be an informant is a debtor MSMEs and credit staff of Bank Jatim Blitar. The results of this study show that Factor of debtor only factor of customer status and credit experience which has influence in the process of non performing loans. While the emphasis of the business factors, seven factors studied had an influence on non performing loans suppression efforts. Recommendations can be given by the author is for employers to continue to pull through innovations in products sold to people not feel bored with the products and can be compete with other entrepreneurs that has a similar product, studying economic trends for credit analysts also necessary in order not wrong in giving credit, as well as for the government to provide training to the MSMEs so that they can further improve their productsKeyword : business characteristics, debtor characteristics, non performing loans